Virat VidyÄ Dalam BrÌ£hadÄranÌ£yaka UpanisÌ£ad - Adnyana, Ida Bagus Putu (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
For ordinary people the universe is a vehicle that is very secret and very difficult to understand. This is due to human limitations in describing it as the impact of knowledge that has not been well developed. Not only ordinary people, even scientists are still very difficult to explain the various events that are displayed by the universe. In scientific disciplines, the conception of the universe can be learned using applied science called cosmology. Cosmology is a scientific discipline that seeks to provide explanations related to the creation of the universe, the phenomena of the universe, as well as threats to the universe or the destruction of the universe. Cosmology deals with the creation, maintenance, and fusion of the universe. All of that is studied in the discipline of cosmology. In Hinduism there is a teaching or knowledge that discusses the same thing, the teachings included in the Vedas are called viratvidyÄ (Hindu Cosmology). This teaching emphasizes the vedas as a basis for thinking to formulate a theory that can describe the ins and outs of the universe. One of the Vedic books that deals with the teaching of viratvidyÄ is Upaniá¹£ad, which is specifically found in the Bá¹›hadâ€˜Ä€raá¹‡yaka Upaniá¹£ad. The viratvidyÄ teachings contained in the Bá¹›hadâ€˜Ä€raá¹‡yaka Upaniá¹£ad will be reviewed using the Hindu perspective. This viewpoint specifically will be discussed with a focus on the very complex primordial element, God. Therefore the concept of this teaching will be reviewed and elaborated based on the perspective of Hindu theology.